Beyond binaries : a way forward for comparativeeducation - Larsen, Marianne (Revista Española de Educación Comparada, 2012)
Binary discourses shape and produce the stories we construct about the field of comparative education. In the first part of this article, I review a set of binary discourses that have characterized social science research since the Enlightenment, including: quantitative-qualitative, nomotheticidiographic, inductive-deductive, and practice-theory. We can think of each of these binaries at opposite ends of a set of spectrums. In the second section of the paper, I show some of the ways in which these binaries have influenced the ways that we write and talk about research within the field of comparative education. I refer to the notion of binary discourses and the productive capacity of these discourses to shape our field. I then outline some critiques of these binaries to demonstrate the inherent limitations of binary discourses, and why we need to move beyond binaries in our research, and in the histories about our field. Finally, I present some tentative conclusions on ways to get ourselves out of the trap of binary thinking. Los discursos binarios moldean y producen los argumentos que construimos sobre la disciplina de la Educación Comparada. En la primera parte de este artículo, analizo un conjunto de discursos binarios que han caracterizado la investigación en Ciencias Sociales desde la Ilustración, incluyendo la cuantitativa-cualitativa, nomotética-idiográfica, inductivadeductiva, y la práctica-teoría. Podemos pensar sobre cada uno de estos discursos binarios como argumentos en los polos de un conjunto de posibilidades. En la segunda sección del artículo, revelo algunos modos en los que estos discursos binarios han influenciado las formas a través de las cuales escribimos y analizamos la investigación en el ámbito de la Educación Comparada. Analizo la noción de discursos binarios y la capacidad productiva de estos discursos de impactar nuestra ciencia. Seguidamente expongo algunas críticas de estos discursos binarios con el objeto de demostrar las limitaciones inherentes a los mismos, y la necesidad de trascenderlos en nuestra investigación y en las historias de nuestra ciencia. Finalmente, avanzo algunas conclusiones tentativas sobre las formas de superar y trascender la trampa del pensamiento binario.